DINAMIKA HARIAN PENUTUPAN MUARA SUNGAI OPAK PADA BULAN OKTOBER-NOVEMBER - , RIA DEWI WIDAYANTI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Opak estuary opening and closing of the dynamics that occur throughout the year. The purpose of this study was to determine how the dynamics of the closure of the mouth of the River Opak, what are the positive and negative impact of closing Opak River estuary, and how to cope with the closure Opak River estuary. The dominant factors are factors such as wind, sea wave, tides, and seasons. The main cause of the closure Opak River estuary is tidal wave and wind The method used is descriptive method and sampling was done by using purposive sampling. This technique is selected based on the purpose of research, meaning the sampling locations selected based on changes in physical phenomena that occur in the study area because of the physical character of an area can be distinguished by physical processes or phenomena that occur. Results of this study was that in October-November is the beginning of the dry season, so the condition of sites still influenced wind from the southeast and south, thus closing the mouth of the dynamics tends to turn toward Opak Northwest. Positively impact the closure of the mouth of the Opak include residents can take advantage of the river mouth to make fish ponds or use it to catch fish because the surface of shallow water, facilitate access of citizens to mobilize. Economically, the income of fishermen, fish farmers, or about the population increased, resulting in increased well-being of their families as well. Negative impacts are upstream frequent flooding, so the fields and rice paddies flooded residents. Simple way that can be done to control the closing of the mouth of the Opak with the smallest risk is the dredging of the river estuary sediments. Opak estuary opening is usually done with the mutual aid or heavy equipment.